SI-KWIRIS: Penerapan Metode R&D dan Waterfall dalam Mengembangkan Sistem Informasi Kwitansi - Arafah, Maharani; Muhammad Dedi Irawan (Journal Of Informatics And Busisnes, 2024)
The rapid development of information technology has affected various fields of life and professions, including the legal field. Mangatas Nasution SH Notary Office is one of the notary offices that still uses a manual transaction recording system. This creates several challenges, such as a slow and inefficient recording process, a high risk of human error, and transaction data that is not centralized and at risk of being lost. This research aims to improve the efficiency and effectiveness of the receipt transaction recording process at the Mangatas Nasution SH Notary Office. The methods used in this research are R&D and waterfall methods. The results showed that the developed receipt information system can improve the efficiency and effectiveness of the process of recording receipt transactions at the Mangatas Nasution SH Notary Office. This system can reduce the time and effort required to make receipts, reduce the risk of human error, and maintain transaction data security. With the receipt information system, the Mangatas Nasution SH Notary Office can improve overall performance and provide better service to clients.